(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2022)
This paper presents the epigraphic novelties from the peninsular southeast published between the years 2017 and 2020: a new reading of a coin legend from near Almodóvar del Río (Córdoba); seven short graffiti on pottery from Lezuza (Albacete); an inscription on a stone object from Puente Tablas (Jaén); an inscription on a fragment of lead, probably from La Mesa, Alcolea del Río (Sevilla); and an inscription on a bronze sheet of unknown provenance.